Longitudinal analyses of gender differences in first authorship publications related to COVID-19. Issue 4 (5th April 2021) - Lerchenmüller, Carolin; Schmallenbach, Leo; Jena, Anupam B; Lerchenmueller, Marc J
Abstract : Objective: Concerns have been raised that the COVID-19 pandemic has shifted research productivity to the disadvantage of women in academia, particularly in early career stages. In this study, we aimed to assess the pandemic's effect on women's COVID-19-related publishing over the first year of the pandemic. Methods and results: We compared the gender distribution of first authorships for 42 898 publications on COVID-19 from 1 February 2020 to 31 January 2021 to 483 232 publications appearing in the same journals during the same period the year prior. We found that the gender gap—the percentage of articles on which men versus women were first authors—widened by 14 percentage points during the COVID-19 pandemic, despite many pertinent research fields showing near equal proportions of men and women first authors publishing in the same fields before the pandemic. Longitudinal analyses revealed that the significant initial expansions of the gender gap began to trend backwards to expected values over time in many fields. As women may have been differentially affected depending on their geography, we also assessed the gender distribution of first authorships grouped by countries and geographical areas. While we observed a significant reduction of the shares of women first authors in almost all countries, longitudinal analyses confirmed a resolving trend over time. Conclusion: The reduction in women's COVID-19-related research output appears particularly concerning as many disciplines informing the response to the pandemic had near equal gender shares of first authorship in the year prior to the pandemic. The acute productivity drain with the onset of the pandemic magnifies deep-rooted obstacles on the way to gender equity in scientific contribution.